(3ePgHGJ GdMRf aj GdeGA hGdNVQI hGdhLg GdMSfs - (3LeGd GdOjf jhSa Hf RcQjG GdeZQHj,J (B1019 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdLhGO GdHQ ef LhOg Ydi GdhQi cGdHMQ s
(3BNQgG (B:s
(3hGSCd GdEdg oMSf GdNGJeI ef aVdg efG hgPj NGJeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3HChdgG hOGNdgG UaMGJ djSJ ef GdeNWhWg HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B231 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B566s
Keywords: (3GdCOHs